2017
DOI: 10.1002/slct.201701263
|View full text |Cite
|
Sign up to set email alerts
|

Accessing the HMF Derivatives from Furfural Acetate through Oxidative Carbonylation

Abstract: Exploring new bulky chemicals from furfural is greatly attractive since its raw biomass resources are not competitive with the food of human beings. Regarding the large market of the sub‐products of hydroxylmethyl furfural (HMF) with the current technical challenges in HMF production from cellulose, transforming furfural and its sub‐products to HMF derivatives may offer an alternative source of HMF sub‐products and a solution to narrow market of furfural. Here, we report a novel route to synthesize the sub‐che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…However, the use of bromine to preactivate the C–H bond of furoic acid to 5-bromofuroic acid may cause concerns about its erosion of the equipment in industrial production. Accordingly, during the exploration of the bromination–carbonylation route for FDCA synthesis, Yin also directly tested the oxidative carbonylation of the furfural platform compound to HMF derivatives …”
Section: Bifunctionalized Furan Monomersmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the use of bromine to preactivate the C–H bond of furoic acid to 5-bromofuroic acid may cause concerns about its erosion of the equipment in industrial production. Accordingly, during the exploration of the bromination–carbonylation route for FDCA synthesis, Yin also directly tested the oxidative carbonylation of the furfural platform compound to HMF derivatives …”
Section: Bifunctionalized Furan Monomersmentioning
confidence: 99%
“…Accordingly, during the exploration of the bromination−carbonylation route for FDCA synthesis, Yin also directly tested the oxidative carbonylation of the furfural platform compound to HMF derivatives. 199 Using furfuryl acetate as the starting compound, these authors explored a Pd(II)/Cu(II)-catalyzed oxidative carbonylation route to ethyl 5-(acetoxymethyl)furan-2-carboxylate, a derivative of HMF, giving a 49.6% yield with 54.4% conversion of substrate under a CO/O 2 (2:1) balloon after reaction at 90 °C for 24 h in a toluene/DMSO solvent. The investigation of the time course of the reaction disclosed that the oxidative carbonylation reaction was highly selective (Figure 1); however, because of the poor efficiency in reoxidizing the reduced Pd(0) back to the active Pd(II) species in the catalytic cycle, the furfuryl acetate substrate was not completely converted under their conditions, even though 1 equiv of Cu(OAc) 2 was added as the cocatalyst.…”
mentioning
confidence: 99%
“…In exploring an alternative route for FDCA synthesis, Pan et al even reported the synthesis of FDCA through disproportionation of furoic acid with the formation of furan, while Pan, Fischer, Dick and Banerjee et al independently explored the C–H carboxylations of furoic acid with CO 2 to FDCA under strong alkaline conditions or with carbonate promoter. We recently developed a four-step synthesis of FDCA from furoic acid through bromination, esterification, carbonylation, and hydrolysis and a one-step synthesis of another HMF derivative through oxidative carbonylation of furfuryl acetate. , Although these new processes are still lengthy or low efficiency, the new developments have convinced us that transforming furfural-based platforms to HMF derivatives is accessible. Here, we present an efficient one-step synthesis of FDCA from 5-bromo-furoic acid through aqueous-phase carbonylation.…”
Section: Introductionmentioning
confidence: 99%
“…27−30 We recently developed a four-step synthesis of FDCA from furoic acid through bromination, esterification, carbonylation, and hydrolysis and a one-step synthesis of another HMF derivative through oxidative carbonylation of furfuryl acetate. 31,32 Although these new processes are still lengthy or low efficiency, the new developments have convinced us that transforming furfural-based platforms to HMF derivatives is accessible. Here, we present an efficient one-step synthesis of FDCA from 5-bromo-furoic acid through aqueous-phase carbonylation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…To this end, the oxidative carbonylation of furfural through C–H activation is the most attractive protocol to obtain C6 chemicals because of its 100% atom-economy. Of note, some of us reported an early example of palladium­(II)-catalyzed oxidative carbonylation of furfural acetate to (5-formylfuran-2-yl)­methyl acetate . Meanwhile, other protocols based on disproportionation or CO 2 insertion involved the C–H bond activation of furoic acid under harsh conditions to afford FDCA. Regarding the low efficiency in C–H activation of furfural for one-step oxidative carbonylation, an alternative protocol is preactivation of C–H bond prior to furfural carbonylation to the bifunctionalized product.…”
Section: Introductionmentioning
confidence: 99%